STUDI KELAYAKAN FINANSIAL PADA PROYEK APARTEMEN BINTARO PLAZA – BREEZE TOWER - Putri Agustina Hidayat; Andi Tenrisukki Tenriajeng (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2021)
The importance of feasibility study research, especially in the financial feasibility of apartment construction, is needed to assess the feasibility of the project. The criteria for financial analysis are NPV, IRR, BCR and PP, then a sensitivity analysis is carried out. The results of the feasibility analysis stated that it was feasible to show the NPV value of Rp. 125,590,204,257, the IRR value was 34.804% which was greater than the MARR value of 11.29%, BCR was 1.596 and PP was 2.36. The calculation of the sensitivity analysis shows that the project is declared feasible if the increase in investment is ≤ 50.852%, the decrease in selling rates is ≤ 27.407% and the decrease in income is ≤ 24.995%.